Yoga, meditation, and mysticism contemplative universals and meditative landmarks - Rose, Kenneth 1951- (Bloomsbury, 2016)
"Pioneering the exploration of contemplative practice and experience with a comparative perspective that ranges over multiple religious traditions, religious studies, philosophy, neuroscience, and the cognitive science of religion, this book is a landmark contribution to the fields of contemplative practice and religious studies"--Provided by publisher.